SAPHO syndrome: pathogenesis, clinical presentation, imaging, comorbidities and treatment: a review - Przepiera-Będzak, Hanna; Brzosko, Marek (Advances in Dermatology and Allergology/Postępy Dermatologii i Alergologii, 2021)
Synovitis, acne, pustulosis, hyperostosis and osteitis (SAPHO) syndrome is a constellation of dermatological and osteoarticular symptoms. The pathogenesis of SAPHO is unknown, but infectious, genetic, immunological and environmental factors may play a role. SAPHO is classified along two different spectrums: pustulo-psoriatic hyperostotic spondyloarthritis and chronic recurrent multifocal osteomyelitis. The typical skin lesions are palmoplantar pustulosis and acne. The sign of arthritis is involvement of the anterior chest wall, most often the sternoclavicular joints. There are no standard treatment recommendations, but nonsteroidal anti-inflammatory drugs, sulfasalazine, methotrexate, antibiotics and biological drugs can be considered.